Structural Contrast in William Blake’s “The Tyger” and “The Lamb” - Novitasari, Eka Agustina; Widyaningrum, Agnes (Prodi Pendidikan Bahasa Inggris, FPBS, Universitas PGRI Semarang, 2024)
Structuralism is a theory focusing on analyzing the structure of a text and the relationship between the elements in order to get the meaning of literary works. Binary opposition is an important concept of structuralism, it is a concept or idea that can gain meaning through its relationship with its opposite. William Blake’s “The Tyger” and the “The Lamb” are two poems contain a lot of meaning that opposites each other. This study address several aspects related to the binary opposition of structuralism in the poems “The Tyger” and “The Lamb” by William Blake: (1) The structural elements in the poems “The Tyger” and “The Lamb” by William Blake. (2) The way “The Tyger” and “The Lamb” by William Blake employ binary oppositions in their structure to convey contrasting themes. (3) The influence of binary opposition on the overall meaning and interpretation of “The Tyger” and “The Lamb” by William Blake. (4) The benefits of using structuralism in poetry for language teaching, and how these can be addressed in teacher training programs. This study applied a qualitative method and context-oriented approach. This study shows that by utilizing structural elements, thematic explorations, tone, language style, and binary oppositions, Blake develops two mutually enhancing yet opposing perspectives on creation and divine existence. The strong and frightening Tyger is in stark contrast with the meek and pure Lamb, representing the intricate nature of life and the various facets of spirituality. This resistance goes beyond just the use of animal imagery, affecting the themes, tone, and language in every poem. Blake prompts readers to confront the contradictions of existence by juxtaposing light with darkness, innocence with experience, and nature with divinity. Studying poetry can be difficult because of different levels of literary skill, teaching methods, and tools, but it provides many academic benefits. Poetry nurtures a greater love for literature, improves creative skills and critical thinking, and aids.